Determinants of Incomplete Childhood Vaccination in Slums of Dhaka and Chattogram Cities, Bangladesh - Billah, Masum; Henderson, Alden Keith; Billah, Syed Muhammad Baqui; Gurley, Emily S (Journal of Health Sciences and Epidemiology, 2025)
During 2011–2015, although national vaccination coverage exceeded 80%, rates among children in urban slums were much lower in Bangladesh. We identified factors associated with incomplete vaccination in slum areas. A case-control study was conducted in Dhaka and Chattogram slums from June 2016 to March 2017. Cases were children aged 12–18 months who missed one or more expanded program on immunization (EPI) recommended doses; controls were fully vaccinated children. Caregivers were interviewed, and adjusted odds ratios (AOR) with 95% confidence intervals (CI) were calculated for significant factors (p<0.05). Total of 603 cases and 1,029 controls were interviewed. Factors associated with incomplete vaccination included negative perceptions of vaccination (AOR 9.2, 95% CI 4.4–19.3), time barriers for caregivers (AOR 2.1, 95% CI 1.5–2.9), and poor health-seeking behavior for other health issues (AOR 2.2, 95% CI 1.6–2.9). Children with older siblings who had incomplete vaccination (AOR 3.4, 95% CI 2.4–4.8) and those with working mothers (AOR 1.7, 95% CI 1.1–2.6) were also at higher risk. Negative perceptions, time constraints, and working mothers contribute to incomplete immunization in slums. EPI should target vaccine hesitancy and extend service hours to improve coverage among working mothers.